2005
DOI: 10.1002/cncr.21599
|View full text |Cite
|
Sign up to set email alerts
|

Local perspective of the impact of the HIPAA privacy rule on research

Abstract: BACKGROUNDThe operational and economic impact of the Health Insurance Portability and Accountability Act (HIPAA) of 1996 was evaluated. The setting was a natural experiment which involved a single‐site, clinical research study that was initiated before the enactment of HIPAA and subsequently modified to be compliant with the new policy.METHODSA formative assessment was conducted of the recruitment process to a clinical trial evaluating the efficacy of an educational strategy to inform Veterans about the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 12 publications
(12 reference statements)
0
33
0
Order By: Relevance
“…Therefore, researchers who are not directly involved in the care of a patient can no longer recruit that patient HIS for patient recruitment 187 directly [31]. There are reports that patient recruitment and follow-up declined significantly after implementation of HIPAA [32,33]. HIS-based patient recruitment needs to be designed carefully to comply with HIPAA requirements, but it seems to be feasible [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, researchers who are not directly involved in the care of a patient can no longer recruit that patient HIS for patient recruitment 187 directly [31]. There are reports that patient recruitment and follow-up declined significantly after implementation of HIPAA [32,33]. HIS-based patient recruitment needs to be designed carefully to comply with HIPAA requirements, but it seems to be feasible [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Second, only cancer patients who received care in 10 community oncology practices were included in this pilot study. However, after the introduction of the Health Insurance Portability and Accountability Act, it may be more expensive to recruit patients to cost of toxicity studies, because health care personnel, rather than research assistants, may be required to identify eligible patients [23]. Third, the choice of the inpatient versus outpatient setting and approach to treatment of febrile neutropenia was based primarily on physician preference, taking into consideration such factors as patient comorbidities and physical examina- tion and laboratory findings.…”
Section: Discussionmentioning
confidence: 99%
“…In [28], it was shown that HIPAA resulted in a 73% decrease in patient accrual after implementation. Since we did not work without it, we cannot say how much effect it had, but it clearly had a negative effect as seen in the earlier study.…”
Section: Discussionmentioning
confidence: 99%